Distinct Phenotypes Induced by Different Degrees of Transverse Aortic Constriction in C57BL/6N Mice - Deng, Haiyan; Ma, Lei-Lei; Kong, Fei-Juan; Qiao, Zengyong (Frontiers in Cardiovascular Medicine, 2021)
The transverse aortic constriction (TAC) model surgery is a widely used disease model to study pressure overload-induced cardiac hypertrophy and heart failure in mice. The severity of adverse cardiac remodeling of TAC model is largely dependent on the degree of constriction around the aorta, the phenotypes of TAC are also different in different mouse strains. Few studies have focus on direct compare phenotypes of TAC model with the different degree of constriction around the aorta, and no one study compares the difference in C57BL/6N mice. In the present study, C57BL/6N mice aged of 10 weeks were subjected to sham surgery, 25G TAC surgery, 26G TAC surgery and 27G TAC surgery for 4 weeks. We then analyzed the different phenotypes induced by 25G TAC, 26G TAC and 27G TAC in c57BL/6N mice in terms of pressure gradient, cardiac hypertrophy, cardiac function, heart failure situation, survival condition and cardiac fibrosis. All C57BL/6N mice subjected to TAC surgery had developed significantly hypertrophy. Mice subjected to 27G TAC had severe cardiac dysfunction, severe cardiac fibrosis, and exhibit characteristics of heart failure at 4 weeks post TAC. Compared with 27G TAC mice, 26G TAC mice showed a much milder response in cardiac dysfunction, cardiac fibrosis compared to 27G TAC, and a very small fraction of 26G TAC group exhibited characteristics of heart failure. There was no obvious cardiac dysfunction, cardiac fibrosis, and characteristics of heart failure observed in 25G TAC mice. Based on our results, we conclude that the 25G TAC, 26G TAC and 27G TAC had induced distinct phenotypes in C57BL/6N mice.